Income Taxes and Tax-Transfer Leases: General Electric's Accounting for A Molotov Cocktail. - Stickney, Clyde P.; Weil, Roman L.; Wolfson, Mark A. (The Accounting Review, 1983)
General Electric uses the equity method of financial accounting for its subsidiary, General Electric Credit Corporation, but consolidates it on the tax return. This note disentangles the amounts and sources of cash payments and refunds for income taxes of the two companies, with special emphasis on the effect of tax-transfer leases. It shows how to estimate the elements of the costs and benefits of tax-transfer leasing. Through tax-transfer leases, General Electric paid its lessees about $350 million in 1981 for benefits estimated to be worth on the order of $500 million, net. These transactions contributed to GE's being able to arrange its tax affairs to receive a refund of $104 million from the U. S. Treasury, while paying over $300 million in taxes to foreign governments and $54 million to state and local governments.